The experiences of female surgeons around the world: a scoping review - Meredith D. Xepoleas; Naikhoba C. O. Munabi; Allyn Auslander; William P. Magee; Caroline A. Yao (BMC, 2020)
Abstract Introduction The Lancet Commission for Global Surgery identified an adequate surgical workforce as one indicator of surgical care accessibility. Many countries where women in surgery are underrepresented struggle to meet the recommended 20 surgeons per 100,000 population. We evaluated female surgeons' experiences globally to identify strategies to increase surgical capacity through women. Methods Three database searches identified original studies examining female surgeon experiences. Countries were grouped using the World Bank income level and Global Gender Gap Index (GGGI). Results Of 12,914 studies meeting search criteria, 139 studies were included and examined populations from 26 countries. Of the accepted studies, 132 (95%) included populations from high-income countries (HICs) and 125 (90%) exclusively examined populations from the upper 50% of GGGI ranked countries. Country income and GGGI ranking did not independently predict gender equity in surgery. Female surgeons in low GGGI HIC (Japan) were limited by familial support, while those in low income, but high GGGI countries (Rwanda) were constrained by cultural attitudes about female education. Across all populations, lack of mentorship was seen as a career barrier. HIC studies demonstrate that establishing a critical mass of women in surgery encourages female students to enter surgery. In HICs, trainee abilities are reported as equal between genders. Yet, HIC women experience discrimination from male co-workers, strain from pregnancy and childcare commitments, and may suffer more negative health consequences. Female surgeon abilities were seen as inferior in lower income countries, but more child rearing support led to fewer women delaying childbearing during training compared to North Americans and Europeans. Conclusion The relationship between country income and GGGI is complex and neither independently predict gender equity. Cultural norms between geographic regions influence the variability of female surgeons' experiences. More research is needed in lower income and low GGGI ranked countries to understand female surgeons' experiences and promote gender equity in increasing the number of surgical providers.